'Scientific' nationalism: N‐VA and the discursive battle for the Flemish nation. Issue 2 (April 2016) - Maly, Ico
Abstract: This paper investigates how the discursive battle for the Flemish nation is waged in the Flemish mass media by politicians of the Flemish nationalist party, the New Flemish Alliance (N‐VA). I focus on the 'new nationalism' that N‐VA politicians advocate as a means to 'banalise' a hot Flemish nationalism. I establish that N‐VA spokespeople and especially their chairman Bart De Wever invoke discursive alliances with established scholars such as Anderson, Hroch, Calhoun and Billig. On the one hand, these alliances are used to sell their nationalism as a non‐ideological or non‐discursive project. On the other hand, the analyses of these intellectuals are used as manuals to 'banalise' a hot nationalism. The concept of 'scientific' nationalism refers to the entextualisation of scientific discourses in order to legitimate and banalise the nationalist project of the party as 'in line with science'.